PENGARUH BRAND EQUITY, PRICE DISCOUNT DAN CONTENT MARKETING TERHADAP LOYALITY MELALUI E-TRUST SEBAGAI VARIABEL INTERVENING PADA UMKM ANANTA BAKERY DI CERMEE KABUPATEN BONDOWOSO - Alvin Ananta; Randika Fandiyanto; Minullah Minullah (Fakultas Ekonomi dan Bisnis, 2025)
The development of the bakery industry in the digital era requires MSME (Micro/Small/Medium Enterprises) such as Ananta Bakery to build strong relationships with consumers to enhance customer loyalty. This study analyses the influence of brand equity, price discounts, and content marketing on customer loyalty, with E-trust as an intervening variable. This research employs a quantitative method with a descriptive approach. A sample of 89 respondents was selected from a population of 760 consumers using Slovin’s formula and a random sampling technique. Data were collected through questionnaires and documentation and analyzed using validity and reliability tests and Structural Equation Modeling (SEM). The findings indicate that brand equity, price discounts, and content marketing significantly affect both e-trust and loyalty. Furthermore, E- Trust is a significant intervening variable that strengthens the influence of the three independent variables on customer loyalty. These findings emphasize the importance of digital marketing strategies and brand management in increasing consumer trust and loyalty for MSMEs in the modern era.